2015
DOI: 10.2528/pierm15081807
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Objects Buried in Layered Media Based on an Equivalent Current Source

Abstract: Abstract-In this paper, a novel algorithm based on an equivalent current source is proposed to reconstruct objects buried in a multilayered medium. First, a radiating current source, one part of the equivalent current source, is obtained directly in closed-form from scattering data via the signalsubspace method. Secondly, a nonradiating current source, the other part of the equivalent current source, is represented with the linear superposition of vectors in the noise-subspace. Finally, the objects and equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, if the object is embedded in a layered media, there is no possibility to approach the object and measure the scattered field at any point around it. In this case, the scattered field can only be measured in the top space, so the available data will be insufficient [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. It is clear that the situation will worsen as the number of layers increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the object is embedded in a layered media, there is no possibility to approach the object and measure the scattered field at any point around it. In this case, the scattered field can only be measured in the top space, so the available data will be insufficient [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. It is clear that the situation will worsen as the number of layers increases.…”
Section: Introductionmentioning
confidence: 99%
“…The main difference of this study from the existing ones in the literature is that it deals with a much more complicated problem geometrically. In most of the studies in the literature, objects to be identified reside in a homogeneous media [1][2][3][4][5][6][7][8][9][25][26][27][28][29][30][31][32][33], layered media with planar interfaces [10][11][12][13][14][15][16][17] or under slightly rough surfaces [18][19][20]. In contrast, the present study deals with a rather complex problem of reconstructing 2D objects embedded in a three-part space with rough interfaces.…”
Section: Introductionmentioning
confidence: 99%